Integrasi Pembelajaran Holistik dalam Pendidikan Islam untuk Penguatan Aspek Spiritual dan Akhlak Peserta Didik - Misrawati, Misrawati; Fadriati, Fadriati; Suryana, Ermis (Lembaga Yasin AlSys, 2025)
Although holistic learning in Islamic education has received attention in several previous studies, research that specifically examines its implementation in strengthening students’ spiritual and moral dimensions in school contexts remains relatively limited. This study aimed to explore in depth how the integration of holistic learning in Islamic education contributes to the reinforcement of students’ spirituality and the habituation of moral behaviour. A qualitative approach with a case study design was employed, involving Islamic education teachers and students selected through purposive sampling. Data were collected through in-depth interviews, classroom observations of the learning process, and document analysis, and were then analysed using thematic analysis to identify key patterns and themes. The findings showed that the integration of holistic learning was manifested in four main themes, namely the integration of spiritual values within the learning process, the habituation of moral conduct through learning activities, the dual role of teachers as facilitators and role models, and students’ generally positive responses to meaningful and contextual learning. These findings affirm that a holistic approach in Islamic education is more capable of comprehensively strengthening students’ spiritual awareness and moral behaviour than approaches that are solely cognitively oriented. Theoretically, this study reinforces the paradigm of holistic Islamic education, while practically it provides direction for schools and educators in designing Islamic education learning that is adaptive to the challenges of the digital era. The study also opens avenues for further research on the development of holistic learning models and the longitudinal measurement of their impact.